EFFORTS TO INCREASE PERFORMANCE THROUGH OPTIMIZATION OF WORK DISCIPLINE - Putra Galuh (Universitas Pamulang, 2022)
Teacher performance is a parameter for school success, and one of the instruments attached is discipline. Logically, disciplined behavior indicates measurable action on a task. Where teachers make rules as work standards, so that everything has a clear basis, strength, and purpose. In the end, discipline can direct teachers to be able to carry out their duties properly and correctly, and be oriented to satisfying results. This study aims to describe and analyze performance improvement based on discipline aspects. The research principle used is quantitative with associative methods. The analysis technique of the research results uses linear regression statistics with the stages of testing including; validity, reliability, classical assumptions, and hypothesis testing. The object of the research was conducted at SMP Muhammadiyah 29 Sawangan, Depok, and the sample of the research was 50 teachers. Research data obtained through the distribution of questionnaires. The results of the study explain, if the performance will increase significantly, if the teacher's discipline behavior increases. Even in the descriptive test, it is known that obedient and obedient attitudes to school rules and regulations are the dominant parameters for good work completion, and have implications for satisfactory resultsKeywords: Teacher, Performance, Discipline, School